2008
DOI: 10.1080/15257770802146452
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of 4-Pyridone-3-Carboxamide-1-ß-D- Ribonucleoside Triphosphate and Its Nucleoside Precursor in the Erythrocytes

Abstract: We recently discovered new nucleotides (4-pyridone-3-carboxamide-1-beta -D-ribonucleoside phosphates) in human erythrocytes. To establish the precursor compound and pathways of nucleotide derivative formation and breakdown, human erythrocytes were incubated for 3 hours with 0.3 mM 4-pyridone-3-carboxamide-1-beta-D-ribonucleoside (4PYR) and erythrocyte concentrations of 4PYR and adenine nucleotides were followed. 4PYR triphosphate increased from 16.1 +/- 0.6 micro M to 74.9 +/- 9.17 and 4PYR monophosphate incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 3 publications
0
21
0
Order By: Relevance
“…It has previously been demonstrated that 4Py-riboside is taken up into intact human erythrocytes in vitro in a reaction carried out by adenosine kinase since it is inhibited by 5'-iodotubericidin, with a net consumption of ATP, and is rapidly converted to the mononucleotide and 4PyTP [ 45 ]. The erythrocyte samples in this study showed a very high accumulation of 4PyTP and 4PyDP, reflecting the much longer timescale and equilibrium within cells obtained in vivo .…”
Section: Resultsmentioning
confidence: 99%
“…It has previously been demonstrated that 4Py-riboside is taken up into intact human erythrocytes in vitro in a reaction carried out by adenosine kinase since it is inhibited by 5'-iodotubericidin, with a net consumption of ATP, and is rapidly converted to the mononucleotide and 4PyTP [ 45 ]. The erythrocyte samples in this study showed a very high accumulation of 4PyTP and 4PyDP, reflecting the much longer timescale and equilibrium within cells obtained in vivo .…”
Section: Resultsmentioning
confidence: 99%
“…4PYR is synthesized with AO involvement primarily in the liver, but it has also been shown that AO is overexpressed in malignant tumors, including breast cancer 16 , 19 . Some 4PYR is distributed to erythrocytes, in which it is rapidly phosphorylated 15 . 4PYR nucleoside phosphorylation into 4PYMP was found to be faster than its subsequent conversion to 4PYTP.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that aldehyde oxidase (AO), the molybdenum cofactor-dependent enzyme, plays a role in 4PYR production by converting nicotinamide riboside 14 . It has also been indicated that adenosine kinase could be responsible for 4PYMP formation 15 . Moreover, earlier data demonstrated the potential involvement of cytosolic 5′-nucleotidase in the degradation of 4PYMP to 4PYR 16 .…”
Section: Introductionmentioning
confidence: 99%
“…This ribosylated pyridone is also found abundantly in circulation in uremic patients. Importantly, it is easily converted to its nucleotide forms (4PYR-MP, 4PYR-DP, 4PYR-TP, [76][77][78][79][80][81][82]. Both the phosphorylated forms of 4PYR and its dinucleotide forms are endogenously generated.…”
Section: The Chemistry Of the Nad(p)(h) Pool The Anabolites And Catabmentioning
confidence: 99%